Mechanical and fracture property optimization of graphene-SiO2-reinforced epoxy-PLA nanocomposites for biomedical applications - Vikram Kedambadi Vasu; Praveena Bindiganavile Anand; Santhosh Nagaraja; Muhammad Imam Ammarullah (Results in Chemistry)
Composite materials are vital in modern engineering due to their superior mechanical properties and versatility. This study examined the effects of adding graphene and SiO2 nanofillers to 75% epoxy − 25% Poly Lactic Acid (PLA) composites on their mechanical and fracture properties. Using bath sonication, twin screw extrusion, and Fused Filament Fabrication (FFF) methods, composites were prepared with filler concentrations of 0.05–0.25 wt%, evenly divided between graphene and SiO2. Mechanical testing revealed that adding up to 0.15 wt% nanofillers significantly enhanced tensile strength, fracture toughness, and flexural strength compared to pure epoxy-PLA. Scanning electron microscopy (SEM) analysis linked these improvements to effective filler-matrix interactions and crack prevention. The biocompatibility of PLA, combined with the added functionalities of graphene and SiO2 highlights the potential of these optimized nanocomposites in biomedical applications.